2014
DOI: 10.1071/cp13314
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of Fusarium graminearum strains from cereals in Italy, and characterisation of their molecular and chemical chemotypes

Abstract: The Fusarium graminearum species complex (FGSC) is a pathogen of durum wheat and other cereals worldwide. The complex consists of at least 15 species that can produce various mycotoxins, including trichothecenes, associated with human and animals toxicoses. In particular, deoxynivalenol (DON), nivalenol (NIV) and their different acetylated derivatives can be produced by the different chemotypes of the complex. In this study, 90 strains, isolated mainly from wheat in Italy and belonging to the FGSC, were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 48 publications
3
32
0
1
Order By: Relevance
“…The 3- isolates belonging to population 2 were included in the analysis of aggressiveness, ten of these were included in the growth rate analysis c 17 3-ADON isolates were included in the analysis of aggressiveness, 16 of these were included in the growth rate analysis ADON chemotype also predominated among a small set of FGSC isolates from an earlier collection of Norwegian cereals (Langseth et al 1999(Langseth et al , 2001, and was found in oat and wheat samples collected between 2009 and 2011 in Sweden, whereas the 15-ADON chemotype was not observed (Fredlund et al 2013;Lindblad et al 2013 (Nielsen et al 2012). Our data add to a growing set of studies indicating a geographical partitioning of trichothecene types (chemotypes or genotypes) throughout Europe, with 3-ADON dominating in Northern Europe, whereas 15-ADON appears predominant in the Western and Southern Europe including the UK (Jennings et al 2004), Belgium (Audenaert et al 2009), Italy (Prodi et al 2009;Somma et al 2014), Luxembourg (Pasquali et al 2010), Poland (Stępień et al 2008), Hungary (Toth et al 2005), Germany (Talas et al 2011), and France (Boutigny et al 2014). …”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The 3- isolates belonging to population 2 were included in the analysis of aggressiveness, ten of these were included in the growth rate analysis c 17 3-ADON isolates were included in the analysis of aggressiveness, 16 of these were included in the growth rate analysis ADON chemotype also predominated among a small set of FGSC isolates from an earlier collection of Norwegian cereals (Langseth et al 1999(Langseth et al , 2001, and was found in oat and wheat samples collected between 2009 and 2011 in Sweden, whereas the 15-ADON chemotype was not observed (Fredlund et al 2013;Lindblad et al 2013 (Nielsen et al 2012). Our data add to a growing set of studies indicating a geographical partitioning of trichothecene types (chemotypes or genotypes) throughout Europe, with 3-ADON dominating in Northern Europe, whereas 15-ADON appears predominant in the Western and Southern Europe including the UK (Jennings et al 2004), Belgium (Audenaert et al 2009), Italy (Prodi et al 2009;Somma et al 2014), Luxembourg (Pasquali et al 2010), Poland (Stępień et al 2008), Hungary (Toth et al 2005), Germany (Talas et al 2011), and France (Boutigny et al 2014). …”
Section: Discussionmentioning
confidence: 58%
“…In addition, isolates with NIV genotypes were absent from our sample, but account for at least 10 % of the FGSC isolates in some other parts of Europe (Jennings et al 2004;Waalwijk et al 2003;Boutigny et al 2014;Stępień et al 2008;Somma et al 2014). The distribution of trichothecene types is likely influenced directly or indirectly by a variety of factors including climate, regional host composition, agricultural practices, and the recent and historical movement of pathogen populations into new areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea, four species within the FGSC were associated with FER and F. graminearum was predominant . A similar situation was also found in France and Italy, where F. graminearum was the main causal agents of FER (Boutigny et al, 2014;Somma et al, 2014). Within the FGSC there are three types of trichothecene mycotoxin producers (chemotypes): (1) nivalenol (NIV) producers and acetylated derivatives; (2) deoxynivalenol (DON) and 3-acetyldeoxynivalenol (3-ADON); and (3) DON and 15-acetyldeoxynivalenol (15-ADON;Miller et al, 1991).…”
Section: Introductionmentioning
confidence: 80%
“…Within the FGSC there are three types of trichothecene mycotoxin producers (chemotypes): (1) nivalenol (NIV) producers and acetylated derivatives; (2) deoxynivalenol (DON) and 3-acetyldeoxynivalenol (3-ADON); and (3) DON and 15-acetyldeoxynivalenol (15-ADON;Miller et al, 1991). The vast majority of F. graminearum isolates reported on maize in France, Korea and China were 15-ADON producers (Boutigny et al, 2014;Lee et al, 2012;Ndoye et al, 2012) while in Europe a small population of NIV producers was found (Boutigny et al, 2014;Ndoye et al, 2012;Somma et al, 2014). Most F. asiaticum on maize in Asia produce NIV (Desjardins and Proctor, 2011;Lee et al, 2012;Ndoye et al, 2012), while F. meridionale and F. boothii isolates seem to be fixed for NIV and 15-ADON production, respectively.…”
Section: Introductionmentioning
confidence: 99%